The Influence of Fear of Missing Out (FOMO), Sales Promotion, and Emotional Motive Mediated Self-Control on Impulsive Buying for Hypebeast Products - Michael Fumar; Ario Setiadi; Stefanie Harijanto; Cindika Tan (Riwayat: Educational Journal of History and Humanities, 2023)
This study investigates the complex interplay of psychological factors influencing impulsive buying behavior for Hypebeast products, a category known for its appeal to consumer trends and exclusivity. The primary objectives are to examine the roles of Fear of Missing Out (FOMO), sales promotion, emotional motives, and self-control in shaping impulsive buying tendencies. The study also explores the potential mediating effect of self-control on the relationship between FOMO, sales promotion, emotional motives, and impulsive buying. Drawing upon a theoretical framework rooted in consumer behavior and psychology, a quantitative research approach was employed. Data were collected through a structured survey administered to a diverse sample of Hypebeast product consumers. The research model was analyzed using advanced statistical techniques, including structural equation modeling (SEM) to assess the direct and mediated effects among the variables. Interestingly, self-control was identified as a partial mediator, attenuating the relationship between FOMO, emotional motives, sales promotion, and impulsive buying. This suggests that individuals with higher self-control may exhibit more regulated buying behaviors even in the face of external pressures and emotional triggers. These results shed light on the multifaceted nature of impulsive buying for Hypebeast products, encompassing both social-psychological factors and individual self-regulation. The implications of this study extend to marketers, practitioners, and researchers aiming to comprehend and influence consumer behavior in the context of trendy and exclusive product categories. By understanding the intricate interplay between FOMO, emotional motives, sales promotion, self-control, and impulsive buying, stakeholders can devise more targeted strategies to engage consumers while promoting responsible purchasing behaviors. Further research avenues include investigating the moderating effects of demographic variables and exploring interventions to enhance consumer self-control in impulsive buying situations.